The complete guide to physical security - Baker, Paul R., 1958- (CRC Press, 2013)
"The Complete Guide to Physical Security gives readers a comprehensive understanding of modern-day physical security best practices. Employing both theory-based and real-world approaches, it examines general business principles as they relate to security. The book goes beyond the concepts of the three G's (guns, gates and guards) and instead explains the importance of physical security to accomplish the overall mission of the organization. The book enables security managers to develop a program that utilizes all security personnel's talents, emphasizing that the security team must work synergistically with all facets of the organization for the ultimate in protection and success"--